Notes on the type specimen of Acanthocalyx delavayi (Caprifoliaceae) at Herbarium of the National Museum of Natural History in Paris (P) - Mu, Qi-Yong; Yu, Chih-Chieh; Xing, Yao-Wu (Phytotaxa, 2020)
Acanthocalyx (DC.) Tiegh. (1909: 199) is a small genus in Caprifoliaceae Jussieu (1789: 210), endemic to the Chinese Hengduan Mountains and adjacent montane regions, yet represents the family’s most characteristic alpine herbaceous perennials in the region. With only three species recognized (A. alba, A. delavayi, A. nepalensis), the taxonomy of Acanthocalyx has not been fully disentangled, and this is particularly due to problem related to the typification of A. delavayi (Franch.) Cannon & Cannon (1984: 14).